2012
DOI: 10.1016/j.jaad.2011.11.963
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of necrolytic acral erythema in patients with chronic hepatitis C virus infection

Abstract: Background Chronic hepatitis C virus (HCV) infection is associated with necrolytic acral erythema (NAE). However, the prevalence of NAE among HCV patients is unknown, and the clinical and histological features have not been well defined. Objective To determine the prevalence, overall clinical features, and cutaneous histopathological characteristics of NAE patients. Methods A cross-sectional study was performed among chronic HCV-infected patients cared for at three Philadelphia hospitals. Patients complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 13 publications
1
34
0
2
Order By: Relevance
“…5 A study recently published showed a prevalence of 1.7% for necrolytic acral erythema among patients with infections caused by hepatitis C virus. 1 The most common location of lesions is the back of feet and toes, but they can also affect the surface of the Achilles tendon, the malleolus, legs and knees. Associated symptoms are pruritus, pain, burning and dysesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 A study recently published showed a prevalence of 1.7% for necrolytic acral erythema among patients with infections caused by hepatitis C virus. 1 The most common location of lesions is the back of feet and toes, but they can also affect the surface of the Achilles tendon, the malleolus, legs and knees. Associated symptoms are pruritus, pain, burning and dysesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…1 It is characterized, in the initial phases, by erythematous or violaceous papules, bullae and erosions. In the late phase, there is onset of well-delimited plaques with erythema on their outer rim, lichenification, secondary hyperpigmentation and fine desquamation on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…There is currently no standard treatment for NAE, although oral zinc, antivirals, topical steroids and phototherapy have been proposed without compelling evidence. The existing literature has contradicting reports as to the efficacy of oral zinc, and phototherapy and topical steroids have shown minimal efficacy . Use of interferon has also been equivocal, with the suggestion that SVR may correlate with clinical improvement, while other reports find interferon regimens ineffective …”
Section: Necrolytic Acral Erythemamentioning
confidence: 99%
“…4,25,28,29 The pathophysiology is unclear, with both direct and indirect theories proposed. The direct theory, supported by evidence that HCV is lymphotropic and that the cryoprecipitate Lichen Planus 2.5-to 4.5-fold increased risk 55,56 Fivefold increased risk 55,56 Porphyria Cutanea Tarda <1-5% 62 50% HCV RNA positivity Up to 275-fold increased risk 62 Necrolytic Acral Erythema 0.2-1.7% 4,91 Near 100% (initially considered pathognomonic for HCV) 86,89,91 Cutaneous HCV in the New Antiviral Era contains high concentrations of viral genome, posits that HCV induces B cells to produce immunoglobulins. Alternatively, the indirect theory proposes that the virus provokes MC via chronic immune stimulation.…”
Section: Association With Hcvmentioning
confidence: 99%
See 1 more Smart Citation